Kompres Air Hangat pada Daerah Aksila dan Dahi Terhadap Penurunan Suhu Tubuh pada Pasien Demam di PKU Muhammadiyah Kutoarjo - Eny Inda Ayu; Winda Irwanti; Mulyanti Mulyanti (Alma Ata University Press, 2015)
Fever is a condition when body temperature 38°C and more. There are also restrictions that took more than 37.8°C, whereas when the body temperature of over 40°C is called a high fever/hyperpyrexia. Fever may be harmfull if you develop a high temperature. Fever or high body temperature can be derived in various ways. Warm compresses a method to lower the body temperature. Found in the fact that research in KRIPMD PKU Muhammadiyah Kutoarjo implementation compress as one independent action to deal with the fever is still often overlooked by patients and families. The purpose of this research was to know the differences between forehead and armpit compress in lowering body temperature among patients with fever at KRIPMD PKU Muhammadiyah Kutoarjo. The Methode of this study used true experimental designs: a two-group pre-post test design. The total population of patient were 40 respondents. The sampling technique was done by consecutive which consisted of 38 respondents. Temperature was measured by thermometer. Data analysis used the t test. T test analysis showed techniques giving a warm compress on the area of the axilla more effective to reduce body temperature than technique of giving a warm compress on the forehead (t=5.879, p=0.000). In conclusion, The technique giving a warm compress on the area of the axilla is more effective to lowering body temperature.